Malignant carcinoid tumour of the oesophagus. - Ready, A R (1989)
A patient with a carcinoid tumour of the oesophagus developed widespread metastases within three years of a successful local resection. Of the seven patients with oesophageal carcinoid tumours so far reported, four have died with widespread metastases.